Updating the knowledge of hepatitis E: new variants and higher prevalence of anti-HEV in Argentina - Munné, María Silvina (2014)
Fil: Munné, María Silvina. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Virología; Argentina.